THE IMPACT OF COMMUNICATION AND MOTIVATION ON EMPLOYEE PERFORMANCE OF ISLAMIC BANKING - Alvindo, Dicky; Siswanto, Siswanto; Supriyanto, Achmad Sani; Retnasih, Nora Ria; Masyhuri, Masyhuri; Hirmawan, Ari Prasetyo (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
This study aims to analyze the effect of communication, motivation and democratic leadership on employee performance. The research approach uses a quantitative approach. The population in this study was 64 employees of Bank Muamalat Indonesia Tbk Kediri Branch Office. The type of sample used in this study is a saturated sample. The data scale uses a Likert scale. Data collection using a questionnaire. Data analysis using multiple linear regression analysis. The results showed that motivation influences employee performance. The communication and democratic leadership variables do not affect employee performance. Meanwhile, the motivation variable influences the performance of Bank Muamalat employees at the Kediri Branch Office.